Effect of summer conditions and shade on behavioural indicators of thermal discomfort in Holstein dairy and Belgian Blue beef cattle on pasture. (21st May 2015) - Van laer, E.; Moons, C. P. H.; Ampe, B.; Sonck, B.; Vandaele, L.; De Campeneere, S.; Tuyttens, F. A. M.
Abstract : Using behavioural indicators of thermal discomfort, that is, shade seeking, panting scores (PS) and respiration rate (RR), we evaluated the effect of hot summer conditions and shade, for a herd of adult Holstein dairy cows and a herd of Belgian Blue beef cows kept on pasture in a temperate area (Belgium). During the summer of 2012, both herds were kept on pasture without access to shade (NS). During the summers of 2011 and 2013 each herd was divided into one group with (S) and one without (NS) access to shade. Shade was provided by young trees with shade cloth (80% reduction in solar radiation) hung between them. For S cows, we investigated how shade use was related to hot conditions as quantified by six climatic indices. The heat load index (HLI), which incorporates air temperature and humidity, solar radiation and wind speed, was the best predictor of the six indices tested. In 2011, there was a relatively high threshold for use of shade. When HLI=90, shade use probability reached 17% for dairy cows and 27% for beef cows. In 2013, however, at HLI=90, shade use probability reached 48% for dairy cows and 41% for beef cows. For animals from the NS treatment we determined the effect of hot summer conditions on RR and PS (with 0=no panting and 4.5=extreme panting). In both types of cattle, an increase in black globe temperature was the best predictor for increasing RR and PS. Furthermore, we determined how the effect of hot summer conditions on RR and PS was affected by the use of shade. Under hot conditions (black globe temperature ⩾30°C), >50% of the animals under shade retained normal PS and RR (PS<1 and RR<90 breaths per minute), whereas normal RR and PS were significantly less prevalent for animals outside shade. Our findings suggest that, even in temperate summers, heat can induce thermal discomfort in cattle, as evidenced by increases in shade use, RR and PS, and that shade increases thermal comfort.